Dynamics and Insights into the Unique Ecological Guild of Fungi in Bacteria-Bioaugmented Anaerobic Digesters - Linda U. Obi; Ashira Roopnarain; Memory Tekere; Jun Zhou; Heng Li; Yuanpeng Wang; Yanlong Zhang; Rasheed A. Adeleke (Journal of Fungi)
Anaerobic digesters host a variety of microorganisms, and they work together to produce biogas. While bacterial and archaeal communities have been well explored using molecular techniques, fungal community structures remain relatively understudied. The present study aims to investigate the dynamics and potential ecological functions of the predominant fungi in bacteria-bioaugmented anaerobic digesters. Eight different anaerobic digesters that contained chopped water hyacinth and cow dung as feedstock at 2% total solids were respectively inoculated with eight different bacterial strains and digested anaerobically in controlled conditions. The diversity and dynamics of the fungal community of the digesters before and after digestion were monitored using high-throughput sequencing of the fungal ITS2 sub-region of the ribosomal gene. The functional potential of the fungal community was predicted using ecological guild analysis. The dominant fungal phyla were (with relative abundance ≥1%) Ascomycota and Neocallimastigomycota. Ascomycota exhibited over 90% dominance in all treatments after anaerobic digestion (AD). Aspergillus sp. was consistently dominant across treatments during AD, while prominent anaerobic fungal genera Anaeromyces, Cyllamyces, and Caeomyces decreased. Ecological guild analysis at genus level showed that the majority of the identified fungi were saprophytes, and diversity indices indicated decreased richness and diversity after AD, suggesting a negative impact of AD on fungal communities in the anaerobic digesters. The multivariate structure of the fungal communities showed clustering of treatments with similar fungal taxa. The findings from this study provide insights into the fungal ecological guild of different bacteria-bioaugmented anaerobic digesters, highlighting their potentials in bacteria-augmented systems. Identification of an anaerobic fungal group within the phylum Ascomycota, beyond the well-known fungal phylum Neocallimastigomycota, offers a new perspective in optimizing the AD processes in specialized ecosystems.